CD and NMR investigation of collagen peptides mimicking a pathological Gly–Ser mutation and a natural interruption in a similar highly charged sequence context. (26th November 2015) - Sun, Xiuxia; Liu, Songqing; Yu, Wenyuan; Wang, Shaoru; Xiao, Jianxi
Abstract: Even a single Gly substitution in the triple helix domain of collagen leads to pathological conditions while natural interruptions are suggested to play important functional roles. Two peptides—one mimicking a pathological Gly–Ser substitution (ERSEQ) and the other one modeling a similar natural interruption sequence (DRSER)—are designed to facilitate the comparison for elucidating the molecular basis of their different biological roles. CD and NMR investigation of peptide ERSEQ indicates a reduction of the thermal stability and disruption of hydrogen bonding at the Ser mutation site, providing a structural basis of the OI disease resulting from the Gly–Ser mutation in the highly charged RGE environment. Both CD and NMR real‐time folding results indicate that peptide ERSEQ displays a comparatively slower folding rate than peptide DRSER, suggesting that the Gly–Ser mutation may lead to a larger interference in folding than the natural interruption in a similar RSE context. Our studies suggest that unlike the rigid GPO environment, the abundant R(K)GE(D) motif may provide a more flexible sequence environment that better accommodates mutations as well as interruptions, while the electrostatic interactions contribute to its stability. These results shed insight into the molecular features of the highly charged motif and may aid the design of collagen biomimetic peptides containing important biological sites.